Peningkatan Pengetahuan Ibu tentang Perawatan Nifas dan Tanda Bahaya melalui Edukasi di Puskesmas Nanggalo - Elda Yusefni; Dewi Susanti; Erwani (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Sixty percent of maternal deaths occur during the postpartum period, and 50% of these deaths happen within the first 24 hours. According to the 2019 Health Profile data of Padang City, Puskesmas Nanggalo has the highest number of visits by high-risk pregnant women, accounting for 80%. The purpose of this Community Service activity is to improve maternal knowledge about postpartum care and danger signs at Puskesmas Nanggalo, Padang City, in 2024. The method of this Community Service activity involves education and promotion to increase the knowledge of mothers and health cadres about postpartum care and danger signs, as well as to provide mothers with an understanding of the benefits of the Maternal and Child Health (MCH) book. The results achieved show that, from 32 pregnant and postpartum women prior to the community service activity, 28.2% had poor knowledge of postpartum care and danger signs. After the community service, there was an increase in knowledge, with 90.6% of mothers having good knowledge and 4.4% having insufficient knowledge. The conclusion is that there was an improvement in maternal knowledge regarding postpartum care and danger signs. It is recommended to enhance the role of husbands in planning, implementation, and monitoring to ensure that mothers receive education about postpartum care and danger signs, as well as health services during pregnancy and postpartum.